The Correlation between Student's Critical Thinking and Reading Comprehension at MAN 2 Gresik - Muad, Mohamad Wildanun; Anwar, Khoirul; Ma'rifah, Ulfah; Ardiyansah, Tri Yuli; Batubara, Riska Widyanita (Jetlal, 2024)
The English language encompasses four essential skills that learners need to master. Among these, reading is crucial, as it involves the ability to comprehend printed words and symbols. Students with strong reading skills are more likely to succeed academically. This study adopted a quantitative approach, emphasizing the outcomes (test results) over the instructional process. The aim was to explore the relationship between students' critical thinking abilities and their reading comprehension. The analysis employs Pearson Correlation because the data types are ordinal and interval. The study sample consisted of 58 students, with a significance level of 5% (0.05). The r-table value for this sample size is 0.4, which is higher than the r-table. This comparison shows that rxy is higher than the r-table, 0.5 > 0.258. Consequently, the alternative hypothesis (Ha) is accepted, and the null hypothesis (H0) is rejected, indicating a positive correlation. From these results, it shows that there is a significant correlation between critical thinking skills and reading comprehension among the students of MAN 2 Gresik. Thus, it can be concluded that the higher the students' critical thinking skills, the better their reading comprehension abilities.